Improved Survival After Pelvic Fracture: 13-Year Experience at a Single Trauma Center Using a Multidisciplinary Institutional Protocol. Issue 1 (January 2016) - Black, Sheena R.; Sathy, Ashoke K.; Jo, ChanHee; Wiley, Marcel R.; Minei, Joseph P.; Starr, Adam J.
Abstract : Objectives: To analyze pelvic fracture mortality rates before and after initiation of a multidisciplinary pelvic fracture protocol. Design: Retrospective database analysis. Setting: Prospective data from our Level-I National Trauma Registry of The American College of Surgeons (NTRACS) database. Patients/Participants: A total of 1682 trauma patients with pelvic fractures from 2000 to 2013 were compared with a control group of 42, 629 without pelvic fractures. Intervention: Initiation of a multidisciplinary institutional protocol to guide the initial management of trauma patients with pelvic fractures. Main Outcome Measurements: Patients were grouped into 3 periods (group 1: 2000–2003, group 2: 2004–2007, group 3: 2008–2013). Multivariate logistic regression analysis was conducted to assess associations between mortality and age, shock (systolic blood pressure less than or equal to 90 mm Hg), head injury (Glasgow Coma Scale less than or equal to 8), Injury Severity Score (ISS), and time period. Results: Unadjusted mortality rates decreased [12.5%–11.0% ( P = 0.72)]; however, ISS increased [19.1–22.7 ( P < 0.01)]. Age, shock, head injury, increasing ISS, and earlier period were significantly associated with mortality. Adjusted mortality decreased over time [odds ratio for 2000–2003 vs. 2008–2013: 2.05, 95% confidence interval = (1.26, 3.33) and odds ratio for 2004–2007 vs. 2008–2013: 1.71, 95% confidence interval = (1.09, 2.67)]. From 2000 to 2003, an unstable fracture pattern in the healthiest cohort significantly increased mortality compared with the stable fracture pattern cohort (8.6% and 0.0%, P < 0.01). In subsequent intervals, there was no statistically significant association between stable versus unstable fracture patterns and mortality. Conclusions: Adjusted pelvic fracture mortality rates have significantly decreased over time. In the healthiest patients with unstable pelvic fractures, the mortality rate is now similar to that of patients with stable fracture patterns. With sustained institutional effort to address pelvic fractures, mortality rates can be diminished. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.